Edwardsiella tarda, a rare human pathogen isolated from a perihepatic abscess: Implications of transient versus long term colonization of the gastrointestinal tract. (2021) - Pham, K.; Wu, Y.; Turett, G.; Prasad, N.; Yung, L.; Rodriguez, G.D.; Segal-Maurer, S.; Urban, C.; Yoon, J.
Abstract: Although gastroenteritis is the most commonly described manifestation of Edwardsiella tarda infection, the pathogenesis and transient or long-term colonization of the gastrointestinal tract of this organism in human disease is not clear. We describe a rare manifestation of E. tarda infection in a perihepatic abscess in the setting of a patient with perforated cholecystitis and its successful eradication following antibiotic treatment.